2020
DOI: 10.1038/s41598-020-62876-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient functional screening of a cellular cDNA library to identify severe fever with thrombocytopenia syndrome virus entry factors

Abstract: The identification of host cell factors for virus entry is useful for the molecular explanation of viral tropisms and often leads to a more profound understanding of virus-induced diseases. Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by SFTS virus. No countermeasures against the disease exist. In this report, we show an efficient method using virus-like particles for the functional screening of a cellular cDNA library to identify SFTS virus entry factors. Two var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Gene perturbation in mammalian cells can be performed either at the endogenous locus of a specific target via effector proteins that activate transcription, such as CRISPR-Cas ( Chavez et al., 2016 ) or exogenously through cDNA expression via inducible or constitutive promoters ( Arnoldo et al., 2014 ). Both CRISPR and cDNA technologies have been leveraged in recent mammalian screens to effectively target genes of interest in an individual or combinatorial manner ( Chavez et al., 2015 , 2016 ; Konermann et al., 2014 ; Qi et al., 2013 ; Horlbeck et al., 2016 ; Bikard et al., 2013 ; Gilbert et al., 2013 ; Zalatan et al., 2015 ; Tak et al., 2017 ; Zhang et al., 2017 ; Liu et al., 2019 ; Yeo et al., 2018 ; Shimojima et al., 2020 ; Parekh et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gene perturbation in mammalian cells can be performed either at the endogenous locus of a specific target via effector proteins that activate transcription, such as CRISPR-Cas ( Chavez et al., 2016 ) or exogenously through cDNA expression via inducible or constitutive promoters ( Arnoldo et al., 2014 ). Both CRISPR and cDNA technologies have been leveraged in recent mammalian screens to effectively target genes of interest in an individual or combinatorial manner ( Chavez et al., 2015 , 2016 ; Konermann et al., 2014 ; Qi et al., 2013 ; Horlbeck et al., 2016 ; Bikard et al., 2013 ; Gilbert et al., 2013 ; Zalatan et al., 2015 ; Tak et al., 2017 ; Zhang et al., 2017 ; Liu et al., 2019 ; Yeo et al., 2018 ; Shimojima et al., 2020 ; Parekh et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The same is probably true for the interactions between DC-SIGN and phenuiviruses. In addition, the human C-type lectins L-SIGN and LSECtin, both closely related to DC-SIGN but expressed on the surface of the liver endothelium [55], are also used as receptors by several phenuiviruses, including RVFV, TOSV, UUKV, and DABV (Table 2) [42,43,46,47]. It is possible that L-SIGN and LSECtin, by acting as receptors on the surface of the liver endothelium, contribute to the hepatic tropism of some phenuiviruses.…”
Section: Cellular Receptors For Phenuiviruses In Mammalian Hostsmentioning
confidence: 99%
“…No deletions were observed in the Hp50-4 strain genome. Based on the determined sequences, plasmids for the reverse genetics of the SFTS virus [ 27 , 41 ] were prepared and used for the preparation of recombinant viruses (recOri for the original and recHp50-4 for Hp50-4) and chimeric viruses (L Hp M Ori whose L and M segments originated from Hp50-4 and the original strains, respectively, and L Ori M Hp whose L and M segments originated from the original and Hp50-4 strains, respectively) ( Fig 2A ). Growth of recOri and recHp50-4 in HeLa cells ( Fig 2B ) and viral antigen distribution in inoculated cells ( Fig 2C ) resembled those of the original and Hp50-4 strains, respectively ( Fig 1A and 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro , but not in vivo , SFTS virus proliferates well in various adherent cell lines including epithelial kidney Vero and hepatocellular HuH-7 cell lines but not in lymphoid cell lines including Raji (B cell origin) and Jurkat (T cell origin) [ 23 25 ]. It has been reported that the expressions of calcium-dependent lectins (C-type lectins, e.g., DC-SIGN, DC-SIGNR, LSECtin) in lymphoid cell lines increased SFTS virus susceptibility, suggesting that SFTS virus infects macrophages via lectins [ 25 27 ]. A recent report on the molecular mechanism(s) of B cell infection suggested increased expression levels of C-C motif chemokine receptor 2, CCR2, were involved [ 28 ].…”
Section: Introductionmentioning
confidence: 99%